Analysis of the influence of the use of the right lane of a stretch of road as a multiple stop on vehicle delays and capacity of adjacent lanes - Soria, Cesar (2023)
Vehicle congestion in a city affects users of public and private transport because it generates loss of time and money. However, this problem becomes more complex when there is no formal bus stop system and there are no defined stop zones for various bus lines. For this reason, this article aims to analyze vehicle delays and the capacity of all lanes in a section of an avenue in the center of Lima. Drone recordings were made to represent in a microsimulation model a section with multiple bus stops that generate traffic congestion. After calibrating and validating the model, 2 scenarios were built. The first scenario does not have bus stops along the section, and in the second scenario, bus stops are ordered and established with optimized distances. The results showed that the presence of multiple stops in the first lane generates an increase in vehicle delays of 114 seconds. In addition, the capacity in the section is 13% less than in a scenario without stops. On the other hand, the optimization of bus stops generates a decrease in vehicular delays of 58 seconds and increases the vehicular capacity in the section by 4.41%.